Battlefield forensics for Persian Gulf States : regional and U.S. military weapons, ammunition and headstamp markings - Mikko, Don; Bailey, William S. (William Scherer) (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2019)
"Battlefield Forensics for Persian Gulf States provides an illustrative reference of various weapons, toolmarks, headstamps, and other traits in order to identify the origins of a variety of guns, casings, and ammunition that can be found in the Middle East."--Provided by publisher.
IV.4 .50 Caliber PenetratorsIV.5 12.7 ? 108mm Penetrators; IV.6 14.4 ? 114mm Penetrators; V: Headstamps; V.1 7.62 ? 39mm-Egyptian; V.2 7.62 ? 39mm-Iranian; V.3 7.62 ? 39mm-Iraqi; V.4 7.62 ? 39mm-Syrian; V.5 7.62 ? 39mm-Polish; V.6 7.62 ? 39mm-Bosnian; V.7 7.62 ? 54mmR-Albanian; V.8 7.62 ? 54mmR-Bulgarian; V.9 7.62 ? 54mmR-Chinese; V.10 7.62 ? 54mmR-Greek; V.11 7.62 ? 54mmR-Iranian; V.12 7.62 ? 54mmR-Romanian; V.13 7.62 ? 54mmR-Iraqi; V.14 7.62 ? 54mmR-Yugoslavian; V.15 7.62 ? 54mmR-Russian; V.16 9 ? 19mm-Iranian; V.17 9 ? 19mm-Iraqi; V.18 9 ? 19mm-Romanian; V.19 9 ? 19mm-Czech
OCLC-licensed vendor bibliographic record.
Keywords: Forensic ballistics -- Persian Gulf States; Forensic ballistics -- United States; Middle East -- Armed Forces -- Firearms -- Markings; United States -- Armed Forces -- Firearms -- Markings; Firearms -- Identification; Firearms -- Persian Gulf States; LAW / Forensic Science; COMPUTERS / Security / General